ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK DAERAH DI PROVINSI BENGKULU - Sari, Dian Purnama; Ilyas, Fitrawati (Universitas Bengkulu, 2016)
This research aims to provide evidence the influence of per-capita income, population, and inflation on local tax revenue in province of Bengkulu during 5 years of observation, that is, since 2009 until 2013. The population in this research are all districts / cities in the province of Bengkulu. Data used in this research is secondary data publicated by Bureau of Statistics Central (BPS) Bengkulu province. The information contains data of local tax revenue, GDP, population, and inflation with a total sample of 10 districts / cities in the province of Bengkulu. Data analyzed using IBM SPSS version 20.0 with a statistical test multiple regression analysis, test the classical assumption of normality test, multicollinearity, heterocedastisity, and autocorrelation test. Hypothesis tested by using F test and t-test. The results of hypothesis testing find that the per-capita income (GDP) has possitive effect on the local tax revenues, while the population has no possitive effect, and inflation has no negative effect on local tax revenues in the district / cities of Bengkulu province.Keywords : Local Taxes, Per-Capita Income, Total population, Inflation